Are enjoyment, anxiety and attitudes/motivation different in English foreign language classes compared to LOTE classes? - Dewaele, Jean-Marc; Saito, Kazuya (Studies in Second Language Learning and Teaching, 2024)
The current study focuses on the effect of the target language on learner emotions and attitudes/motivation. More specifically, it investigates whether the status and prestige of English results in more positive learner emotions and attitudes/motivation compared to less prestigious languages other than English (LOTE). Statistical analyses of a database of 360 students in an English-speaking university in Kuwait enrolled in English, German, Spanish and French as foreign language classes revealed that the LOTE learners (who also knew English) reported significantly more foreign language enjoyment (FLE), equal levels of foreign language classroom anxiety (FLCA) and – surprisingly – lower levels of attitudes/motivation than their peers studying English. Due to confounding variables, it is impossible to establish the cause of the difference with certainty, but this outcome does show that a stronger motivation to study English does not necessarily translate into more enjoyment in class. In other words, while FLE and attitudes/motivation typically correlate, they are independent concepts.